Aligning Corporate Strategy with Environmental, Social, and Governance (ESG): A Case Study of InfraTrans - Secioputri, Grace Lucy; Putro, Utomo Sarjono (Integrasi Sains Media, 2025)
As Environmental, Social, and Governance (ESG) principles become central to corporate strategy, transportation infrastructure firms face mounting pressure to integrate sustainability into their operations. This study investigates how InfraTrans—a pseudonym for one of the toll road operators in Indonesia—can align its corporate strategy with global ESG frameworks to enhance transparency, regulatory compliance, investor confidence, and long-term resilience. Employing a qualitative case study design, the research draws on semi-structured interviews with key internal and external stakeholders, document analysis, and ESG benchmarking against the GRI and SASB standards. The findings reveal critical gaps in InfraTrans’s ESG practices, notably in emissions tracking, supplier assessments, infrastructure lifecycle management, and digital reporting. To address these, the study proposes seventeen ESG-oriented strategies derived through SWOT and TOWS matrix analyses. These are organized into two categories: ESG Foundations, focusing on governance, disclosure, audit systems, and employee capacity-building; and ESG Pillars, which emphasize digital integration, sustainable infrastructure development, and stakeholder engagement. Each strategy is explicitly linked to identified ESG disclosure gaps and has been validated by industry experts to ensure relevance, feasibility, and alignment with Indonesian regulatory frameworks and investor expectations. The study concludes with a phased implementation roadmap, offering actionable insights for transportation infrastructure companies—particularly in emerging markets—seeking to elevate their ESG performance and strategic positioning.